INVESTIGATION OF DIELECTRIC PROPERTIES OF NONIDEAL PLASMA IN THE FRAMEWORK OF PSEUDOPOTENTIAL MODEL - Voronkov, V.V. (Recent Contributions to Physics, 2008)
Spectrum and damping decrements of Langmuir and ionsound waves in nonideal plasma are found. Potential considering quantum effects of diffraction is used. Local fields are considered through the theory of linear dielectric response and numerical solution of Ornstein-Zernicke equation in hypernetted approach.